Provisions Regarding Low Heritage In The Compilation Of Islamic Law (Study In Nagari Koto Gadang, Koto Besar District Dharmasraya District) - Delfia Eka Putri; Cizmeci Jaewon; Smallridge Simone (Yayasan Adra Karima Hubbi, 2023)
The purpose of this research is to explain the distribution of low inheritance that occurs in Nagari Koto Gadang. The research method used in this study is a qualitative method, in which data collection uses interview techniques from the Nagari Koto Gadang community. In Minangkabau custom, there are two types of inheritance that are inherited, namely high inheritance and low inheritance. Low inheritance assets are assets originating from one family's livelihood assets, in the form of rice fields, fields purchased from other parties. In this study it can be concluded thatThis low inheritance can be inherited through customary law and Islamic law. Because there is a similarity, that is, low inheritance is an inheritance in Minangkabau custom, and low inheritance can be donated according to Islamic law.